Tracheostomy in infants with severe bronchopulmonary dysplasia: A review - Akangire, Gangaram; Manimtim, Winston (Frontiers in Pediatrics, 2023)
In recent years, there has been a significant increase in pediatric tracheostomy, particularly in children less than 1 year of age. The most common indication for tracheostomy in this age group is long-term mechanical ventilation due to severe bronchopulmonary dysplasia (BPD). As advanced technology in neonatal intensive care has improved survival of extremely premature and peri-viable infants, the number of infants with severe BPD who become ventilator-dependent has increased correspondingly. Infants with severe BPD who remain invasively ventilated by 36 weeks’ corrected age have significantly greater risk for needing a tracheostomy. Evidence shows that tracheostomy in severe BPD may improve short- and long-term respiratory and neurodevelopmental outcomes. However, there is significant variation among centers in the indication, timing, intensive care management, and follow-up care after hospital discharge of infants with severe BPD who received tracheostomy for chronic ventilation. The timing of liberation from the ventilator, odds of decannulation, rate of rehospitalization, growth, and neurodevelopment are all clinically important outcomes that can guide both clinicians and parents to make a well-informed decision when choosing tracheostomy and long-term assisted ventilation for infants with severe BPD. This review summarizes the current literature regarding the indications and timing of tracheostomy placement in infants with severe BPD, highlights center variability in both intensive care and outpatient follow-up settings, and describes outcomes of infants with severe BPD who received tracheostomy.